1965
DOI: 10.2466/pr0.1965.16.3.906
|View full text |Cite
|
Sign up to set email alerts
|

Running Activity of Weanling Rats under Food or Water Deprivation

Abstract: Two groups of 1 0 weanling rats were placed in running wheels and terminally deprived of either food or water. No significant differences in the amounts of running between groups were observed. However, the food-deprived animals showed significantly greater weight losses and survived for a shorter period. The contention that young animals characteristically show different activity patterns as a consequence of food or water deprivation was not supported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1967
1967
1970
1970

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Numerous studies have demonstrated that food deprivation increases locomotor activity of rats in a variety of activitymeasuring devices (e.g., Campbell, 1964;Treichler & Feeney, 1965). Several physiological factors have been invoked to account for this increase, but thus far no discrete physiological change has been identified as the primary substrate for deprivation-induced increases in activity (cf.…”
mentioning
confidence: 99%
“…Numerous studies have demonstrated that food deprivation increases locomotor activity of rats in a variety of activitymeasuring devices (e.g., Campbell, 1964;Treichler & Feeney, 1965). Several physiological factors have been invoked to account for this increase, but thus far no discrete physiological change has been identified as the primary substrate for deprivation-induced increases in activity (cf.…”
mentioning
confidence: 99%